Person-organizational fit dan work engagement: peran gender dan masa kerja sebagai moderator - Hendryadi Hendryadi; Sitti Marijam Thawil (Faculty of Economics and Business Mulawarman University, 2019)
This study aims to examine the relationship between person-organizational fit (P-O fit) and work engagement, and how gender and tenure would moderate its relationships. Data were collected from 245 respondents from various business companies in Jakarta. The regression hierarchy is used to test the research model. The analysis shows that P-O Fit is closely related to work engagement. The gender is proven to moderate the relationship between P-O fit and work engagement, whereas tenure is not statistically significant. The implications of this finding for management need to consider the suitability of individuals with the organization in the initial selection process to ensure that HR has a high work engagement. This study is initial research that examines the moderating effects of gender and work tenure on the relationship between P-O fit and work engagement.